2020
DOI: 10.1111/bjet.13056
|View full text |Cite
|
Sign up to set email alerts
|

From experiencing to expressing: A virtual reality approach to facilitating pupils’ descriptive paper writing performance and learning behavior engagement

Abstract: Due to the lack of life experience and situational experience, it is difficult to arouse pupils’ inner motivation and interest in writing. Therefore, the early stage of Chinese writing may be a challenge for Chinese pupils. In order to solve this problem, a spherical video‐based virtual reality (SVVR) experience learning system was developed to help pupils improve their writing performance and interest. To evaluate the effectiveness of the proposed approach, an experiment was carried out in a primary school in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 31 publications
3
59
0
Order By: Relevance
“…Therefore, it may take more time to cultivate their learning motivation. Huang et al and Yang et al have reported that a short study period may not be sufficient for improving students' learning motivation and that students need more time and learning experience to develop their abilities [74,75]. It may also be due to the difficulty, change, and flexibility of the makeup certification course itself and because students are under pressure to obtain certificates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may take more time to cultivate their learning motivation. Huang et al and Yang et al have reported that a short study period may not be sufficient for improving students' learning motivation and that students need more time and learning experience to develop their abilities [74,75]. It may also be due to the difficulty, change, and flexibility of the makeup certification course itself and because students are under pressure to obtain certificates.…”
Section: Discussionmentioning
confidence: 99%
“…For landscape architecture students, the proposed SV-IVR learning system in this study is feasible and effective. The fact that SV-IVR technology increases students' learning performance has also been proved by many researchers [27,29].…”
Section: Discussionmentioning
confidence: 80%
“…In terms of self-efficacy, one possible explanation is that a short period of studying may not increase students' self-efficacy. Huang et al [6] and Yang et al [29] also implied that students need more time and learning experience to develop their capabilities. All students in the experimental group were exposed to this learning system for the first time, so a 50 min learning experience may not have been sufficient to improve their self-efficacy, and self-efficacy needs to be cultivated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that the short learning period did not improve the elderly participants’ self-efficacy and learning satisfaction. As Huang et al and Yang et al pointed out, elderly people need more time and learning experience to develop their abilities [ 31 , 45 ]. Moreover, the elderly participants in the experimental group were exposed to calligraphy AR for the first time, thus, three weeks of learning might not be long enough to improve their self-efficacy and learning satisfaction.…”
Section: Discussionmentioning
confidence: 99%